Loss of C9orf72 Enhances Autophagic Activity via Deregulated mTOR and TFEB Signaling. - Janet Ugolino; Yon Ju Ji; Karen Conchina; Justin Chu; Raja Sekhar Nirujogi; Akhilesh Pandey; Nathan R Brady; Anne Hamacher-Brady; Jiou Wang (PLoS Genetics, 2016)
The most common cause of the neurodegenerative diseases amyotrophic lateral sclerosis and frontotemporal dementia is a hexanucleotide repeat expansion in C9orf72. Here we report a study of the C9orf72 protein by examining the consequences of loss of C9orf72 functions. Deletion of one or both alleles of the C9orf72 gene in mice causes age-dependent lethality phenotypes. We demonstrate that C9orf72 regulates nutrient sensing as the loss of C9orf72 decreases phosphorylation of the mTOR substrate S6K1. The transcription factor EB (TFEB), a master regulator of lysosomal and autophagy genes, which is negatively regulated by mTOR, is substantially up-regulated in C9orf72 loss-of-function animal and cellular models. Consistent with reduced mTOR activity and increased TFEB levels, loss of C9orf72 enhances autophagic flux, suggesting that C9orf72 is a negative regulator of autophagy. We identified a protein complex consisting of C9orf72 and SMCR8, both of which are homologous to DENN-like proteins. The depletion of C9orf72 or SMCR8 leads to significant down-regulation of each other's protein level. Loss of SMCR8 alters mTOR signaling and autophagy. These results demonstrate that the C9orf72-SMCR8 protein complex functions in the regulation of metabolism and provide evidence that loss of C9orf72 function may contribute to the pathogenesis of relevant diseases.